Role of Plasmodium vivax Dihydropteroate Synthase Polymorphisms in Sulfa Drug Resistance - Pornthanakasem, Wichai (Antimicrob Agents Chemother, 2016)
Dihydropteroate synthase (DHPS) is a known sulfa drug target in malaria treatment, existing as a bifunctional enzyme together with hydroxymethyldihydropterin pyrophosphokinase (HPPK). Polymorphisms in key residues of Plasmodium falciparum DHPS (PfDHPS) have been characterized and linked to sulfa drug resistance in malaria. Genetic sequencing of P. vivax dhps (Pvdhps) from clinical isolates has shown several polymorphisms at the positions equivalent to those in the Pfdhps genes conferring sulfa drug resistance, suggesting a mechanism for sulfa drug resistance in P. vivax similar to that seen in P. falciparum. To characterize the role of polymorphisms in the PvDHPS in sulfa drug resistance, various mutants of recombinant PvHPPK-DHPS enzymes were expressed and characterized. Moreover, due to the lack of a continuous in vitro culture system for P. vivax parasites, a surrogate P. berghei model expressing Pvhppk-dhps genes was established to demonstrate the relationship between sequence polymorphisms and sulfa drug susceptibility and to test the activities of PvDHPS inhibitors on the transgenic parasites. Both enzyme activity and transgenic parasite growth were sensitive to sulfadoxine to different degrees, depending on the number of mutations that accumulated in DHPS. K(i) values and 50% effective doses were higher for mutant PvDHPS enzymes than the wild-type enzymes. Altogether, the study provides the first evidence of sulfa drug resistance at the molecular level in P. vivax. Furthermore, the enzyme inhibition assay and the in vivo screening system can be useful tools for screening new compounds for their activities against PvDHPS.